Language Planning and Policy, Law and (Post)Colonial Relations in Small Island States: A Case Study - Herman Bröring; Eric Mijts (Social Inclusion, 2017)
Language planning and policy (LPP) in postcolonial island states is often strongly (co)determined by the former colonizer’s state tradition. Comparable to the examples of the development of LPP in Cabo Verde (Baptista, Brito, & Bangura, 2010), Haiti (DeGraff, 2016), and Mauritius (Johnson, 2006; Lallmahomed-Aumeerally, 2005), this article aims to illustrate and explain in what way the current situation of the dominance of Dutch in governance, law and education in Aruba (and Curaçao) can only be explained through path dependency and state tradition (Sonntag & Cardinal, 2015) in which, time and again, critical junctures, have not led to decisions that favour the mother tongue of the majority of the population (Dijkhoff & Pereira, 2010; Mijts, 2015; Prins-Winkel, 1973; Winkel, 1955). In this article, three perspectives on LPP in small island states are explored as different aspects of the continuation of the former colonizer’s state tradition and language regime. The first part will focus on the (non-)applicability of international treaties like the European Charter for Regional or Minority Languages (ECRML) on the challenges of small island states. The point will be made that international treaties, like the ECRML, do not (currently) provide sufficient basis for the protection of languages in former colonial islands and for the empowerment of individuals through language rights. The second part explores the meaning of fundamental legal principles and specific demands, deduced from international treaties. The point will be made that the structure of the Kingdom of the Netherlands brings with it several limitations and obstacles for the autonomous development of LPP. The third part will focus on the way in which current Aruban legislation reflects the dominance of Dutch in governance, the judiciary and education. While bearing in mind that choices for legislation on language for governance, the judiciary and education are rooted in very diverse principles, a critical reading of existing legislation reveals an interesting dynamic of symbolic inclusive legislation and exclusive practices through language restrictions that favour the Dutch minority language. Recent research, however, demonstrates that law/policy and practice are not aligned, as such creating an incoherent situation that may call for a change in legislation and policy.